Aberrant DNA methylation patterns in microsatellite stable human colorectal cancers define a new marker panel for the CpG island methylator phenotype. Issue 4 (13th October 2021) - Gebhard, Claudia; Mulet‐Lazaro, Roger; Glatz, Dagmar; Schwarzfischer‐Pfeilschifter, Lucia; Schirmacher, Peter; Gaedcke, Jochen; Weichert, Wilko; Reuschel, Edith; Dietmaier, Wolfgang; Rehli, Michael
Abstract: A distinct group of colorectal carcinomas (CRCs) referred to as the "CpG island methylator phenotype" (CIMP) shows an extremely high incidence of de novo DNA methylation and may share common pathological, clinical or molecular features. However, there is limited consensus about which CpG islands (CGIs) define a CIMP, particularly in microsatellite stable (MSS) carcinomas. To study this phenotype in a systematic manner, we analyzed genome‐wide CGI DNA methylation profiles of 19 MSS CRC using methyl‐CpG immunoprecipitation (MCIp) and hybridization on 244K CGI oligonucleotide microarrays, determined KRAS and BRAF mutation status and compared disease‐related DNA methylation changes to chromosomal instability as detected by microarray‐based comparative genomic hybridization. Results were validated using mass spectrometry analysis of bisulfite‐converted DNA at a subset of 76 individual CGIs in 120 CRC and 43 matched normal tissue samples. Both genome‐wide profiling and CpG methylation fine mapping segregated a group of CRC showing pronounced and frequent de novo DNA methylation of a distinct group of CGIs that only partially overlapped with previously established classifiers. The CIMP group defined in our study revealed significant association with colon localization, either KRAS or BRAF mutation, and mostly minor chromosomal losses but no association with known histopathological features. Our data provide a basis for defining novel marker panels that may enable a more reliable classification of CIMP in all CRCs, independently of the MS status. Abstract : What's new? The CpG island methylator phenotype (CIMP) is an important feature of colorectal carcinoma (CRC). No consensus exists, however, on a marker panel that defines CIMP in CRC, neither for microsatellite stable (MSS) nor for microsatellite instable disease. Here, to better understand associations between markers and CIMP CRC, the authors analyzed genome‐wide CpG island DNA methylation profiles in CRC. Genome‐wide profiling and CpG methylation fine mapping revealed frequent de novo DNA methylation of a group of CpG islands. The CIMP group, the basis for a novel marker panel, was associated with colon localization, KRAS and BRAF mutation, and minor chromosomal losses.